DILI (drug induced liver injury) in a 9-month-old infant: a rare case of phenobarbital-induced hepatotoxicity - Anna Paola Pinna; Gabriella Locci; Maria Furno; Daniela Fanni; Gavino Faa; Anna Maria Nurchi (Journal of Pediatric and Neonatal Individualized Medicine, 2013)
Phenobarbital is one of the most commonly prescribed antiepileptic drugs in childhood, but it can rarely cause serious adverse effects, such as hepatotoxicity that includes a broad clinical spectrum (from isolate hypertransaminasemia to acute liver failure). We describe a case of DILI in a 9-month-old infant caused by chronic therapy with phenobarbital.